Transport and thermodynamic properties of KFSI in TEP by operando Raman gradient analysis - Zhao, J; Jagger, B; Olbrich, LF; Ihli, J; Dhir, S; Zyskin, M; Ma, X; Pasta, M (American Chemical Society, 2024)
Understanding and characterizing the transport and thermodynamic properties of electrolytes are critical for optimizing battery performance. In this study, we employ operando Raman gradient analysis (ORGA) to characterize the concentration-dependent diffusion coefficient, transference number, ionic conductivity, and thermodynamic factor of potassium bis(fluorosulfonyl)imide (KFSI) in triethyl phosphate (TEP), an ideal model system and one of the most promising K-ion battery electrolytes. ORGA demonstrates results consistent with conventional state-of-the-art methods while proving to be significantly more electrolyte- and time-efficient. Additionally, we probe, for the first time, the concentration-dependent transport and thermodynamic properties of KFSI-TEP, providing key parameters for K-ion battery modeling.